2010
DOI: 10.1177/0016986210383155
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Acceleration on High-Ability Learners: A Meta-Analysis

Abstract: Current empirical research about the effects of acceleration on high-ability learners’ academic achievement and social— emotional development were synthesized using meta-analytic techniques. A total of 38 primary studies conducted between 1984 and 2008 were included. The results were broken down by developmental level (P-12 and postsecondary) and comparison group (whether the accelerants were compared with same-age, older, or mixed-age peers). The findings are consistent with the conclusions from previous meta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
102
0
4

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 110 publications
(119 citation statements)
references
References 25 publications
11
102
0
4
Order By: Relevance
“…In addition, three quarters of our sample had previously taught students who had skipped a grade, and the overwhelming majority of teachers experienced this as positive or at least as not exclusively negative. This finding is congruent with the overall positive effects of grade skipping on students' development as reported in empirical studies (Kulik, 2004;Rogers, 2015;Steenbergen-Hu & Moon, 2011). Still, teachers' positive experiences are encouraging given that Vock, Penk, and Köller (2014) had previously shown in a large unselected German student sample that a substantial proportion of students who had skipped a grade had cognitive abilities only slightly above average and only modest scores on standardized achievement tests; apparently, teachers had encouraged or at least allowed many students to skip a grade when the students did not have the necessary preconditions for acceleration and among whom the authors subsequently found a significantly increased rate of class repeaters.…”
Section: Explaining the Odds Of Teachers' Recommendations For Grade Ssupporting
confidence: 89%
See 1 more Smart Citation
“…In addition, three quarters of our sample had previously taught students who had skipped a grade, and the overwhelming majority of teachers experienced this as positive or at least as not exclusively negative. This finding is congruent with the overall positive effects of grade skipping on students' development as reported in empirical studies (Kulik, 2004;Rogers, 2015;Steenbergen-Hu & Moon, 2011). Still, teachers' positive experiences are encouraging given that Vock, Penk, and Köller (2014) had previously shown in a large unselected German student sample that a substantial proportion of students who had skipped a grade had cognitive abilities only slightly above average and only modest scores on standardized achievement tests; apparently, teachers had encouraged or at least allowed many students to skip a grade when the students did not have the necessary preconditions for acceleration and among whom the authors subsequently found a significantly increased rate of class repeaters.…”
Section: Explaining the Odds Of Teachers' Recommendations For Grade Ssupporting
confidence: 89%
“…Results on the social and emotional development of students who have skipped a grade are more controversial, which may be partly attributable to the great variety of social and psychological outcomes under investigation. Whereas some studies have found no or slightly positive overall effects (Kulik, 2004;Steenbergen-Hu & Moon, 2011), a recent meta-analysis concluded that there appear to be moderate positive effects on students' socioemotional well-being (Rogers, 2015). Therefore, grade skipping can be an effective way of supporting gifted students and students with excellent academic achievements.…”
Section: Research-article2016mentioning
confidence: 99%
“…This begs the question of whether teachers fully understand that acceleration is one type of current research-based programming for gifted students (Colangelo, Assouline, & Gross, 2004;Rogers, 2004;Steenbergen-Hu, & Moon, 2011). Can they truly support what they do not know?…”
Section: Discussionmentioning
confidence: 99%
“…But education researchers generally agree that acceleration benefits the vast majority of gifted children socially and emotionally, as well as academically and professionally 7 . Skipping grades is not the only option.…”
Section: On the Fast Trackmentioning
confidence: 99%